A bicenter study on adjuvant surgery following treatment with tyrosine kinase inhibitors in patients with advanced lung adenocarcinoma. (16th April 2018) - Fournel, Ludovic; Falcoz, Pierre-Emmanuel; Mansuet-Lupo, Audrey; Garelli, Elena; Lococo, Filippo; Alifano, Marco
Abstract: OBJECTIVES: A small number of patients with advanced pulmonary adenocarcinomas treated with tyrosine kinase inhibitors (TKIs) was subsequently considered eligible for surgery. Our goal was to report the clinical characteristics, pathological features and prognosis of these patients with the aim of exploring the feasibility of this strategy of care. METHODS: We retrospectively reviewed the medical files of 19 patients in whom systemic treatment, including TKIs, resulted in a possible stabilization of the disease such that they were considered eligible for surgery (adjuvant surgery). RESULTS: Lobectomy, pneumonectomy or segmentectomy was performed in 68.4%, 26.3% and 5.3% of cases, respectively. Limited fibrotic tissues were detected intraoperatively in 8 patients who received TKIs as the sole systemic treatment. The postoperative course in the hospital was uneventful in 13 (68.4%) cases; 3 (15.8%) patients suffered major complications. The post-pneumonectomy early morbidity rate was 60%. A pathological analysis of the tumours showed that the median rate of fibrosis was 32.5% (0–100); of viable neoplastic tissue, 25.0% (0–90); and of necrosis, 12.5% (0–80%). Four tumours (21.1%) exhibited no viable tumour cells. The fibrosis ratio was higher in patients older than 60 years ( P  = 0.01) and in those treated with erlotinib ( P  = 0.03). The 3- and 5-year overall survival and disease-free survival rates were 79.5%/39.8% and 44.4%/29.6%, respectively. Pneumonectomy and <50% fibrosis or >30% viable tumour cells in the pathological specimens were factors significantly associated with lower disease-free survival. CONCLUSIONS: In a subset of highly selected patients, adjuvant lung surgery following treatment with TKI showed a large spectrum of histological changes in the pathological specimens and encouraging preliminary survival results. Pending further research, it may prove a relatively reliable and safe therapeutic choice, except when an extensive resection like a pneumonectomy is planned.